2008
DOI: 10.1007/s11239-008-0238-6
|View full text |Cite
|
Sign up to set email alerts
|

The smoker’s paradox after successful fibrinolysis: reduced risk of reocclusion but no improved long-term cardiac outcome

Abstract: Background In smokers treated with fibrinolysis for ST-elevation myocardial infarction (STEMI) a paradoxical beneficial short-term outcome has been reported. This was attributed to favorable clinical and angiographic baseline variables and a better response to fibrinolysis. During follow-up infarct artery reocclusion is an important prognosticator. We studied the effects of smoking on reocclusion and long-term cardiac outcome after successful fibrinolysis. Methods In the Antithrombotics in the Prevention of Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Our study demonstrates that trauma patients experience a "smoker's paradox" similar to that of cardiovascular patients. 1,2,5,6,23,44 We found that there was an independent association between smoking status and mortality and complication outcomes in severely injured patients, with smoking greatly reducing the risk of death even after adjusting for potential confounders such as age. Several potential mechanisms may explain the protective effect of smoking following trauma and future studies investigating therapeutic applications of these findings should be conducted.…”
Section: Resultsmentioning
confidence: 70%
“…Our study demonstrates that trauma patients experience a "smoker's paradox" similar to that of cardiovascular patients. 1,2,5,6,23,44 We found that there was an independent association between smoking status and mortality and complication outcomes in severely injured patients, with smoking greatly reducing the risk of death even after adjusting for potential confounders such as age. Several potential mechanisms may explain the protective effect of smoking following trauma and future studies investigating therapeutic applications of these findings should be conducted.…”
Section: Resultsmentioning
confidence: 70%
“…The term "smoker's paradox" was coined in the thrombolysis era when the use of fibrinolytic agents was the main strategy for STEMI reperfusion, and the high thrombogenicity state in smokers might have predicted a more favorable response to fibrinolysis [28]. However, this response was not confirmed by all thrombolysis trials, such as the GUSTO-1 trial which did not find any difference in the prevalence of thrombi or residual stenosis between smokers and non-smoker receiving thrombolysis [29]. In the contemporary era of primary PCI the studies are less supportive of the presence of this paradox when correction for differences in baseline variables was considered [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…myocardial infarction, stroke, peripheral vascular disease) has had smoking identified as a risk factor [1][2][3][4] for the acute ischemic event, there are a number of investigations that demonstrate a protective effect of smoking. Specifically in the setting of acute myocardial infarction (AMI), decreases in early/late mortality, reocclusion after thrombolysis, and restenosis rate after percutaneous intervention are lower in patients that smoke and continue to smoke [5][6][7][8][9][10]. This counterintuitive phenomenon is commonly referred to as the 'smoker's paradox', with smoking patients in general presenting 10 years earlier and with more severe infarction than their nonsmoking counterparts [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically in the setting of acute myocardial infarction (AMI), decreases in early/late mortality, reocclusion after thrombolysis, and restenosis rate after percutaneous intervention are lower in patients that smoke and continue to smoke [5][6][7][8][9][10]. This counterintuitive phenomenon is commonly referred to as the 'smoker's paradox', with smoking patients in general presenting 10 years earlier and with more severe infarction than their nonsmoking counterparts [5][6][7][8][9]. However, in an investigation involving young (approximately 40 years old), age-matched cohorts of smokers and nonsmokers, the paradox was still present [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation